Mining claim No. 3 below Newton Creek, Alaska, approximately 1901. - Hegg, Eric A., 1867-1948 (1901)
Newton Creek, vicinity Nome on the Seward Peninsula. Caption on image: "No. 3 below Newton" Original image in Hegg Album 27, page 22. Original photograph by Eric A. Hegg 1797; copied by Webster and Stevens 125.A Nome Gold Rush.